THE INFLUENCE OF RELIGIOUS AWARENESS ON STUDENT ETHICS AT UIN KIAI HAJI ACHMAD SIDDIQ JEMBER WITH LECTURERS' RELIGIOUS BEHAVIOR AS AN INTERVENING FACTOR - Nuruddin (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
This article aims to describe the role of religious consciousness in etiquette, with lecturers’ religious behavior as an intervening variable, among students of the Faculty of Tarbiyah at the Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java. This study uses a quantitative method with a causal explanatory approach. The sample was calculated by multiplying 11 indicators by an interval of 7, yielding a total of 77 students selected using the side quota technique. Descriptive analysis uses the SPSS version 27.1 application to calculate the percentage of tendency. Hypothesis testing in SmartPLS 4.0 involves two stages: measurement model testing and structural testing. The research findings conclude that religious consciousness influences student etiquette by 46%. Religious consciousness influences lecturers’ religious behavior by 56.4%. Lecturers’ religious behavior influences student etiquette by 43.7%. Keywords: Religious Consciousness; The Etiquette; Lecturers In Religious Behavior; Students. Abstrak Artikel ini bertujuan untuk mendeskripsikan peran kesadaran beragama terhadap adab tata krama dengan variabel perilaku keagamaan dosen sebagai variabel intervening pada mahasiswa fakultas tarbiyah di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Jawa Timur. Penelitian ini menggunakan metode kuantitatif. Dengan pendekatan causal eksplanatori. Sampel dihitung dengan mengalikan 11 indikator dengan interval 7 yang diperoleh jumlah responden sebanyak 77 mahasiswa yang dipilih menggunakan teknik kuota samping. Analisis deskriptif menggunakan aplikasi SPSS versi 27.1 untuk menghitung persentase kecenduran. Sedangkan pengujian hipotesis menggunakan aplikasi smart-pls versi 4.0 dengan dua tahap pengujian yaitu uji model pengukuran, outer model, measurement model dan uji structural. Temuan penelitian menyimpulkan bahwa; kesadaran beragama berpengaruh terhadap tata krama mahasiswa sebesar 46,%. Kesadaran beragama berpengaruh terhadap perilaku keagamaan dosen sebesar sebesar 56,4%. Perilaku keagamaan dosen berpengaruh terhadap tata krama mahasiswa sebesar43.7%. Kata kunci: Kesadaran Religius; Etiket Dosen; Perilaku Religius; Mahasiswa